PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KETERAMPILAN METAKOGNISI PADA MATERI LAJU REAKSI - Nurmiati, Euis; Dahlan, Dahlan; Rudi, La (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2021)
This research is related to the development of student worksheets (LKPD) based on metacognition skills in one of the Chemistry learning materials, namely the reaction rate. This material was chosen because this material contains metacognition skills as one of the aspects that must be achieved in Core Competencies (KI). Metacognition skills can help students become self-regulated learners who are responsible for their own learning progress and adapt their learning strategies to achieve the demands of the assignment. The importance of LKPD based on metacognition skills is developed so that students understand how the task is carried out and monitor their own learning progress. Therefore, the student worksheet contains components of metacognition skills such as planning, monitoring (monitoring), evaluating (evaluating), and revising (revising). The purpose of this study was to develop metacognition-based student worksheets (LKPD) on the material on reaction rates. The type of research being carried out by researchers is research and development using the 4-D model, namely define, design, development, and disseminate stages. The instrument used was a content assessment / validation sheet. Furthermore, the second data is related to a questionnaire related to the implementation of the LKPD. The results of the questionnaire are as follows: (1) LKPD media 65.45%, (2) LKPD material 71.25%, (3) LKPD language 78%, and (4) LKPD metacognition skills 77.5% with average percentage -The mean of all scores is 73.05%.